Size distribution and growth pattern of mangrove crab Scylla serrata in Takalar District - Musfira, Musfira; Kantun, Wayan; Kabangnga, Arnold; Ardianza, Reza (Acta Aquatica: Aquatic Sciences Journal, 2024)
Crab is one of the coastal fisheries resources that has high economic value and has been intensively utilized. This study aims to analyze the size of the carapace width and weight of the S. serrata crab. The research was conducted using the survey method, through measurement at the crab landing and marketing site. The results showed that the carapace width of male mud crabs ranged from 59.1-149.3 mm (87.35 ± 12.36 mm), with weights ranging from 30.0-560 g (121.68 ± 46.11 g). Female mud crabs had carapace widths ranging from 64.0-172 mm (88.16 ± 14.24 mm), with weights ranging from 40.0-790 g (128.14 ± 64.20 g). The growth pattern of male and female mud crabs is negative allometric, with carapace width increasing faster than crab weight. Crabs that meet the size that can be caught based on carapace width are 13 crabs (2.32%) and based on weight are 118 crabs (21.03%). The crabs caught predominantly did not meet the catchable size.Keywords: Carapace Width; Catchable Size; Growth Pattern of Scylla serrata; Weight